Marking behavior of the giant anteater Myrmecophaga tridactyla (Mammalia: Myrmecophagidae) in Southern Brazil - Braga,Fernanda G. (2010)
This research presents novel data on tree marking by the giant anteater, a large Neotropical mammal threatened in the state of Paraná and other areas of Brazil, and nearly threatened worldwide. Field work was carried out in the municipality of Jaguariaíva, Paraná (Southern Brazil) with the goal of evaluating the pine marking behavior of the giant anteater and ascertaining whether wildfires interfere with it. Anteater marks were searched for on the trunks of pine trees in stands as well as pine trees dispersed throughout the landscape. For each pine tree, the following features were recorded: height, diameter breast height (DBH), height of first branch, presence/absence of scratch marks, geographical location, substrate, and matrix. The total number of scratches, scratch directions, scratch length, and height of top mark were also recorded. The scratches were defined as horizontal or vertical. Tree scratching was directly observed in three instances. Ninety-one trees were measured in the study area. The differences between marked and non-marked pines were significant for DBH and height of first branch. All scratches were found on pines dispersed throughout the landscape. Trees with horizontal and vertical marks were significantly different in terms of DBH, first branch height, and top mark height. After a wildfire that affected part of the study area, 54% of the previously marked trees were marked anew. We suggest that the marking behavior is used for communication between conspecifics with overlapping home ranges, possibly during the mating season. Additionally, we advance the hypothesis that pine marking behavior becomes more frequent with increased population stress due to anthropic interference.